2017
DOI: 10.1126/science.aai7685
|View full text |Cite
|
Sign up to set email alerts
|

Gene duplication can impart fragility, not robustness, in the yeast protein interaction network

Abstract: Robustness of protein networks It is thought that gene duplication helps cells maintain genetic robustness, but this seems not to be the whole story. Diss et al. investigated the fate of protein-protein interactions among duplicated genes in yeast. Some interacting duplicates evolved mutual dependence, resulting in a more fragile system. This finding helps us understand the evolutionary trajectories of gene duplications and how seemingly redundant genes can increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
114
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(120 citation statements)
references
References 50 publications
6
114
0
Order By: Relevance
“…However, if both are expressed at a comparable level, both would be expected to affect cell proliferation in a comparable manner. In addition, Diss et al () showed that physical dependency between interacting paralogs is often asymmetrical, the lowly expressed copy being affected by the deletion of the highly expressed one more than in the reciprocal condition. They suggested that this asymmetry could derive from the fact that the lowly expressed one may be post‐translationally stabilized by the most expressed one.…”
Section: Resultsmentioning
confidence: 99%
“…However, if both are expressed at a comparable level, both would be expected to affect cell proliferation in a comparable manner. In addition, Diss et al () showed that physical dependency between interacting paralogs is often asymmetrical, the lowly expressed copy being affected by the deletion of the highly expressed one more than in the reciprocal condition. They suggested that this asymmetry could derive from the fact that the lowly expressed one may be post‐translationally stabilized by the most expressed one.…”
Section: Resultsmentioning
confidence: 99%
“…We propose that seed strains are in the stage of gene expansion. Despite the role of gene duplications in species diversification and the acquisition of new functions, this process can also lead to genomic instability [33]. …”
Section: Discussionmentioning
confidence: 99%
“…Half of the paralogous pairs tested required each other's presence to maintain their interaction profile [58].…”
Section: Study Of Protein-protein Interaction Rewiring In Evolutionmentioning
confidence: 99%
“…While some interactions were shared, others were found to be isoform-specific. The degree to which interactions are shared may be an approximate measure of shared function, and may allow for the elucidation of redundancy in protein interaction networks [58]. Post-translational modifications (PTMs) also contribute to protein complexity and mediate conditional interactions; recent efforts to identify PPIs that create or rely on PTMs have been reviewed by Woodsmith and Stelzl [67].…”
Section: Considerations For Future Interactome Mapping Efforts Proteimentioning
confidence: 99%